Technology-Enhanced Performance-Based Feedback to Support Teacher Practice and Child Outcomes. (August 2021) - Coogle, Christan Grygas; Storie, Sloan; Ottley, Jennifer R.; Rahn, Naomi L.; Kurowski-Burt, Amy
We investigated the effect of real-time technology-enhanced performance-based feedback delivered during three different routines on teacher practice and child outcomes. Participants were three early childhood special education teachers and three focus preschool children identified with autism spectrum disorder. We used a multiple-probe single-case design to provide real-time technology-enhanced performance-based feedback across child-led, teacher-led, and mealtime routines. We collected generalization data across a fourth novel routine, clean-up. We analyzed teachers' use of communicative antecedents and consequences, children's responses to antecedents, and children's expressive communication. Real-time technology-enhanced performance-based feedback enhanced teachers' use of communicative antecedents and consequences, and when teachers used antecedents, children responded to these opportunities and practiced their expressive communication.